A Cholera Outbreak of the Vibrio cholerae O1 El Tor Variant Carrying Classical CtxB in Northeastern Thailand in 2007 - Okada, Kazuhisa (The American Society of Tropical Medicine and Hygiene, 2010)
Cholera outbreaks occurred in Thailand in 2007. Isolates from the northeastern regions were analyzed. Interestingly, the outbreak strain was identified as biotype El Tor; serotype Ogawa with cholera toxin B subunit gene (ctxB) of the classical type and CTX prophage repressor gene of the El Tor type. The clone was genetically closely related to pulsotype H, which is predominantly found in India. It was probably introduced into Thailand recently.